Loneliness in hermingway`s a clean, well-lighted place a graduating paper submitted in partial fulfillment of the bachelor degree in english literature - Adnan Hidayat Purnama (Faculty of Adab and Cultural Sciences State Islamic University Sunan Kalijaga, 2016)
yt,1/ws.c.1